"Lof zij het land waar ik geboren ben" - A. Demedts. - D'Haese, Jan; Witdouck, Romain (St.-Baafs-Vijve : A. Demedtshuis, 1986)
Baertsoen, Albert ; Boulez, Jules ; Cantré, Jozef ; Caullet, Albert ; Claus, Emile ; De Boeck, Felix ; De Bruycker, Jules ; De Cock, Xavier ; de Cocker, Henri ; De Coene, Jozef ; De Coninck, René ; Deleu, Arthur ; De Smet, Gust ; Ensor, James ; Huys, Modest ; Lippens, Piet ; Malfait, Hubert ; Lippens, Piet ; Malfait, Hubert ; Masereel, Frans ; Minne, George ; Montigny, Jenny ; Moreau, Pierre Louis ; Permeke, Constant ; Saverijs, Albert ; Schelck, Maurice ; Servaes, Albert ; Sijs, Maurice ; De Giessen, Arie Van ; Van Mulders, Modest ; Viérin, Emmanuel
biografie
Nederlands
boek